2023
DOI: 10.1002/chem.202301739
|View full text |Cite
|
Sign up to set email alerts
|

Structural Expansion of Cyclohepta[def]fluorene towards Azulene‐Embedded Non‐Benzenoid Nanographenes

Abstract: Non‐benzenoid non‐alternant nanographenes (NGs) have attracted increasing attention on account of their distinct electronic and structural features in comparison to their isomeric benzenoid counterparts. In this work, we present a series of unprecedented azulene‐embedded NGs on Au(111) during the attempted synthesis of cyclohepta[def]fluorene‐based high‐spin non‐Kekulé structure. Comprehensive scanning tunneling microscopy (STM) and non‐contact atomic force microscopy (nc‐AFM) evidence the structures and confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Successful synthesis and isolation of kinetically protected derivatives of 1 was accomplished by Horii et al and the ground states were reported as singlet states in all cases that were examined. 21,22 Benzo-extended derivatives of 1 were also reported 23,24 with the work of Lombardi et al 23 showing that the considered derivatives have singlet ground states and very low-lying triplet states with singlet triplet gaps as small as 0.002 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 78%
“…Successful synthesis and isolation of kinetically protected derivatives of 1 was accomplished by Horii et al and the ground states were reported as singlet states in all cases that were examined. 21,22 Benzo-extended derivatives of 1 were also reported 23,24 with the work of Lombardi et al 23 showing that the considered derivatives have singlet ground states and very low-lying triplet states with singlet triplet gaps as small as 0.002 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 78%
“…To reduce the computational cost, we have focused our theoretical studies on only one of the two identical reaction sites (lower segment of the NG in Figure 2a). Based on reported literature, [61,62] we have also considered that the hydrogen atoms situated at the sp 3 carbon atoms of the two five‐membered rings are already detached from P (denoted as the initial state ( IS ) in Figure S2), once the molecule is deposited on Au(111) surface. In the second step, the dehydrogenation of the methyl group, corresponding to steps IS → IM1 , occurs.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, recent efforts have been focused on synthesizing and characterizing NGs with an open‐shell (magnetic) ground state, as they hold potential for next‐generation quantum technology [40] . However, up to date, the realization of atomically precise open‐shell non‐benzenoid NGs remains limited, [41–44,64] and the role of non‐alternant topologies in tailoring their structural, optical, electronic, and magnetic properties is still far from being fully understood [45–54] …”
Section: Introductionmentioning
confidence: 99%
“…Experiments have been performed by scanning tunneling microscopy (STM) and spectroscopy (STS) operated at low temperature (5 K) under ultrahigh-vacuum (UHV) conditions, supported by density functional theory (DFT) calculations. To probe the molecular geometric deformation, the high spatial resolution in real space provided by STM offers the possibility to investigate the planarity of molecules at the single-molecule level. We employ STM manipulation to convert the molecules from nonplanar to planar configuration, revealing that the intermolecular interactions within the molecular islands stabilize the nonplanar configuration. We compared the electronic structures by using STS measurements.…”
Section: Introductionmentioning
confidence: 99%